Jimmy Carter and the Anglo-American 'Special Relationship' - Robb, Thomas K. (Edinburgh Studies in Anglo-American Relations : ESAAR, 2022)
Reveals the true nature of relations between the US and the UK during the Carter presidencyThomas K. Robb draws upon a wealth of previously classified documents to reveal that relations between Britain and the United States of America during Carter's presidency were riven with antagonism and disagreement. Contrary to existing interpretations, even the most 'special' aspects of intelligence and nuclear cooperation were not immune to high-level political tension.Robb exposes the true competitive nature of the relationship during Carter's presidency, as well as providing an original understanding to how both countries approached the breakdown of superpower détente; the subject of international human rights promotion; the tackling of common economic and energy challenges and to the Anglo-American nuclear and intelligence relationship